Desempenho de cultivares de soja em função do tamanho das sementes - Camozzato, Vitor Arlindo (2007)
Due to the great importance in the world-wide agribusiness, the soybean crop has been focus of innumerable research. For the fact of that the seeds assuming a major role in the implantation and productivity of farming. It was compared productivity of seeds produced from seed lots with large and small seeds. The study was undertaken during the crop year of 2006/07, in Pato Branco, PR. Three varieties were used, CD-214RR, NK-8350 and V-MAX with seed sizes of 5,5 and 6,5 millimeters in thickness. The evaluations were weight of a thousand seeds, number of pods per plant and number of seeds per pod. Based on the results, the following conclusions were taken: 1- Seed size does not affect productivity, and 2- Cultivars can present different answers in their yield component s regarding the size of the seed